Sir Pete the Brave - Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
When a dragon kidnaps Lady Callie, Sir Pete the Brave must come to her rescue.
Ages 4-8.
Guided reading level H.
Keywords: Cats -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Dragons -- Juvenile fiction; Readers (Primary); Cats -- Fiction; Knights and knighthood -- Fiction; Dragons -- Fiction; Cats; Dragons; Knights and knighthood; Children's stories; Fiction; Juvenile works